A Qualitative Cross-Sectional Study Describing the Challenges of Value-Added Tax as Perceived by Low Economic Group Consumers in Durban, Kwa-Zulu Natal - Sewraj, Remalia Teshandre (The IIE, 2020)
This qualitative research study aimed to describe the challenges faced by lower economic group consumers. These challenges arise due to the payment of VAT on most products. Value-added tax is an indirect tax that is charged on certain goods and services. Due to the current VAT rate, retail businesses are struggling to keep its loyal consumers and attract new shoppers. In addition, this study aimed to identify ways retail store can retain its consumers. The researcher used the Consumer Decision-Making Process theory to determine the purchasing decisions of lower economic group consumers. This theory will inform businesses on the consumer decisions so marking and pricing tactics can be adjusted accordingly. This research report was based on an interpretivism paradigm of research. Face-to-face interviews were used as the data collection tool. The data was analysed using a qualitative content analysis method.
Keywords: Value added tax (VAT); Low economic group consumers; Durban; Perceptions